2008
DOI: 10.3164/jcbn.2008010
|View full text |Cite
|
Sign up to set email alerts
|

Intervention with Delivery of Diabetic Meals Improves Glycemic Control in Patients with Type 2 Diabetes Mellitus

Abstract: Summary The aim of this study was to investigate the effects of a diabetic meal delivery system on glycemic control over a 12 month period in patients with type 2 diabetes. A total of 77 patients with type 2 diabetes were assigned randomly into three dietary intervention groups: group M, diabetic meal delivery; group D, individual dietary counseling; and group C, conventional dietary education. In group M, HbA1c levels decreased significantly from 8.2 ± 1.2% to 7.4 ± 0.8% after 12 months (p<0.05), while in gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 12 publications
(6 reference statements)
1
56
0
Order By: Relevance
“…Twenty‐seven RCTs met the eligibility criteria and were included in the review, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐seven RCTs met the eligibility criteria and were included in the review, as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…11-13 One delivered meals, but patients were free to choose both the frequency and the period of delivery, and patients were encouraged to change their exercise habits. 13 Thus, that study examined the effects of the combination of delivered meals and exercise, and there were no changes in BMI during the course of the 1-year trial. The other 2 studies each lasted for 1 year, but the special meals consisted of 7 meals per week, which were delivered weekly, and there was no description of BW nor were clinical data provided.…”
Section: Discussionmentioning
confidence: 99%
“…studies, meals were not delivered daily to the individual's home, 11,12 and no remarkable changes in BW were observed, 13 despite a long study period of 1 year. In addition, no clinical data were provided.…”
Section: Noda K Et Almentioning
confidence: 99%
“…H 2 can reach relatively high concentrations quickly, and excessive H 2 can be eliminated from the body via breathing, causing no side effects ). In addition, therapeutic H 2 effects on humans have been reported for diabetes mellitus type 2 (Imai et al, 2008), hemodialysis (Nakayama et al, 2010), inflammatory myopathies (Ito et al, 2011), radiotherapy for liver cancer (Kang et al, 2011), and acute erythematous skin diseases (Ono et al, 2012). H 2 can be administered through intravenous injection or drink.…”
Section: Discussionmentioning
confidence: 99%